2000
DOI: 10.1002/(sici)1521-1878(200004)22:4<311::aid-bies1>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Spiny legs and prickled bodies: new insights and complexities in planar polarity establishment

Abstract: Epithelial cells can be polarized along two axes, namely in the apical‐basolateral axis and in the horizontal plane of the epithelium. Vertebrate examples of planar polarization include aspects of skin development or features in internal organs, such as the inner ear epithelium. In insects like Drosophila, adult cuticular structures show planar polarization. Studies on planar polarity in Drosophila have identified several genes that regulate this process. Notably, the Frizzled receptor and its signaling cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…It has been shown previously that one of the identified genes, encoding the tropomyosin-like protein Ci-Trop, is directly regulated by Ci-Bra, possibly in conjunction with additional regulatory factors (Di Gregorio and Levine, 1999). Another gene of the second category, Ciona intestinalis prickle (Ci-pk1/2), a homologue of the Drosophila planar cell polarity gene prickle (Gubb et al, 1999;Mlodzik, 2000;Tree et al, 2002) has been identified recently in zebrafish and in Xenopus (Wallingford et al, 2002;Carreira-Barbosa et al, 2003;Takeuchi et al, 2003;Veeman et al, 2003). prickle expression in Xenopus gastrula stage embryos is reminiscent of Xbra expression and has been shown to be up-regulated by Brachyury overexpression in Xenopus animal cap cells and to function not only in convergent extension movements during Xenopus and zebrafish gastrulation but also in neuronal migration in zebrafish (CarreiraBarbosa et al, 2003;Takeuchi et al, 2003, Veeman et al, 2003.…”
Section: Brachyury Downstream Targetsmentioning
confidence: 99%
“…It has been shown previously that one of the identified genes, encoding the tropomyosin-like protein Ci-Trop, is directly regulated by Ci-Bra, possibly in conjunction with additional regulatory factors (Di Gregorio and Levine, 1999). Another gene of the second category, Ciona intestinalis prickle (Ci-pk1/2), a homologue of the Drosophila planar cell polarity gene prickle (Gubb et al, 1999;Mlodzik, 2000;Tree et al, 2002) has been identified recently in zebrafish and in Xenopus (Wallingford et al, 2002;Carreira-Barbosa et al, 2003;Takeuchi et al, 2003;Veeman et al, 2003). prickle expression in Xenopus gastrula stage embryos is reminiscent of Xbra expression and has been shown to be up-regulated by Brachyury overexpression in Xenopus animal cap cells and to function not only in convergent extension movements during Xenopus and zebrafish gastrulation but also in neuronal migration in zebrafish (CarreiraBarbosa et al, 2003;Takeuchi et al, 2003, Veeman et al, 2003.…”
Section: Brachyury Downstream Targetsmentioning
confidence: 99%
“…2). In particular, studies in Drosophila have shed light on how planar polarity is established and has led to the identification of signaling components that control planar polarity (for review, see Eaton 1997;Shulman et al 1998;Mlodzik 1999Mlodzik , 2000Strutt and Strutt 1999;Bray 2000;Adler and Lee 2001;Strutt 2001). Among these components, the Rho GTPases have emerged as key players and will be discussed in detail below.…”
Section: Planar Polaritymentioning
confidence: 99%
“…The results of studies examining the generation of similarly polarized structures in the wing and eye of Drosophila have suggested that the Wingless/Wnt signaling pathway could play a key role in the generation of uniform orientation (reviewed by Shulman et al, 1998;Mlodzik, 2000;Adler and Lee, 2001).…”
Section: Introductionmentioning
confidence: 99%